Relationship between cooling time and neurological outcomes in targeted temperature management. (7th March 2022) - Ahn, Seong Jun; Kim, Yong Hwan; Lee, Jun Ho; Lee, Dong Woo; Hwang, Seong Youn; Lee, Byung Kook; Cho, In Soo; Oh, Sang Hoon; Cha, Kyoung‐Chul; ,
Abstract: Objectives: The relationship between cooling time (CT) variables and neurological outcomes is controversial. We evaluated the relationship between CT and neurological outcomes in out‐of‐hospital cardiac arrest (OHCA) patients treated with targeted temperature management (TTM). Methods: We conducted a multicenter, prospective, and registry‐based study of OHCA survivors treated with TTM. CT was defined as the time from restoration of spontaneous circulation to achievement of the target temperature. The primary outcome was a favorable neurological outcome at 6 months. Multilevel logistic regression analysis was performed to test the relationship between CT and the primary outcome. Results: Overall, the favorable neurological outcome rates at 6 months were 29.8% in 937 patients. When CT was stratified into categories of 0–3, 3.1–6, 6.1–9, 9.1–12, and >12 h, according to 3‐h intervals, the primary outcome rates were 8.2%, 22.7%, 35.5%, 44.7%, and 44.5%, respectively (p < 0.001). Significant differences were not found in multilevel logistic regression analysis; the adjusted odds ratios (95% confidence interval) of each category for the primary outcome compared to the 0–3‐h group were 0.81 (0.32 to 2.04), 0.77 (0.30 to 2.01), 1.26 (0.43 to 3.68), and 1.06 (0.37 to 3.06). Conclusions: We did not find a relationship between CT and neurological outcomes at 6 months.